Pengaruh Komitmen Organisasi, Lingkungan Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada Pondok Pesantren Al Ishlah Assuyuthi - Wahyu Eko Romadhon; Wahyu, Brahma; Syahputra, Erwin (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This study aims to analyze the influence of organizational commitment, work environment, and job satisfaction on employee performance at Pondok Pesantren Al Ishlah Assuyuthi. This research employs a quantitative approach with a total population of 50 respondents, all of whom were used as the research sample through a non-probability sampling technique, specifically a saturated sample method. Data were collected using questionnaires distributed to all employees and analyzed using the SPSS 25.0 software. The analysis included validity and reliability tests, classical assumption tests, multiple linear regression, partial (t) tests, and simultaneous (F) tests. The results indicate that organizational commitment has a significant partial effect on employee performance. Similarly, the work environment and job satisfaction variables also show a significant partial influence on employee performance. Simultaneously, organizational commitment, work environment, and job satisfaction have a significant effect on improving employee performance at Pondok Pesantren Al Ishlah Assuyuthi. These findings suggest that increasing employees’ organizational commitment, creating a supportive work environment, and enhancing job satisfaction are crucial factors in optimizing employee performance within educational institutions such as Islamic boarding schools.